A influência da experiência do cliente na recompra de serviços de saúde - Maeda, George Masatochi de Campos (2019)
Academic studies with different perspectives have addressed and investigated the role of customer experience management in business. In order to better understand this subject a bibliographic research was carried out in this dissertation, It presents the concepts of customer experience, customer experience management, customer journey, attributes of the point of care, customer satisfaction, and, finally, the customer repurchase intention. Subsequently, a statistical model was proposed, analyzed by the multiple linear regression and logistic regression procedures, in order to identify the most significant emergency room service attributes for the customer experience; and the influence of customer experience on the customer repurchase intention. Emergency room service is the object studied. The results obtained in this study combined with the available academic production about the concept of customer experience extended the understanding about the customer experience management in the emergency room service. The results of the statistical model presented the following results: a) The customer experience has a positive influence on the customer repurchase intention of emergency room service. b) Out of 15 attributes of emergency room service measured in the survey, only 5 are significant and have high influence on customer experience.